The Cartel Proof in Business Competition Law: From the Rule of Reason to Per Se Illegal - Santosa, Anak Agung Gede Duwira Hadi; Dewi, Lily Karuna; Megayani, Ni Ketut Ngetis Megi (JURNAL AKTA, 2023)
Per se illegal approach is used to deal with cartel cases, which emphasises that cartel acts that have fulfilled the elements in the formulation of the article and are proven to violate the regulation without the need to prove the impact of such acts so that the enforcement of cartels can be resolved more quickly. This article intends to review and evaluate the Anti-Monopoly Law and PUTS in Indonesia regarding how the rule of reason approach is used to handle cartel cases in Indonesia. The research uses the normative method, namely legal research by processing library materials or secondary data. This article suggests that the more appropriate approach to handling cartel cases in Indonesia is the per se illegal approach, given that proving the act with this approach is easier and shorter to do so that the settlement of cartel cases can be resolved quickly. In addition, Indonesian civil procedure law does not yet recognise and regulate economic evidence, so economic evidence cannot be used to prove the case. Whereas economic evidence in the form of economic analysis of the impact of a cartel is mandatory in cartel settlement using the rule of reason approach. By evaluating the performance of the rule of reason in handling cartel cases in Indonesia, this article argues that it is important to change the wording of articles in the Anti-Monopoly Law and PUTS in Indonesia which previously used the rule of reason approach in handling cartel cases to apply the per se illegal approach.